REFLEKSI BUDAYA ABORIJIN DAB INVASI ANGLO-KELTIK DALAM ALINTA, THE FLAME, KARYA HYLLUS MARIS DAN SONIA BORG - Syam, Essy (Jurnal Ilmu Budaya, 2008)
Alinta, the flame reflects a aboriginal society in which Aboriginal people are shown as nomadic society who loves nature. The love to nature is based on the perception that Aboriginal people are united with the nature and this leads to their wise treatment in preserving the nature. Unfortunately, the coming of Anglo-Celtic to Australian continent destroyed the life of the Aboriginal people and its culture. The Anglo-Celtic people burnt the Aboriginal houses, stole their lands and did abusive treatments like hitting them or raping the women.